The effects of homestay capabilities on homestay performance in Sabah - Cynthia Robert Dawayan; Stephen Laison Sondoh Jr.; Geoffrey Harvey Tanakinjal; Bonaventure Boniface; Sorayah Nasip (Sarawak Research Society, 2021)
Although homestays have been in the Malaysian tourism industry for over a decade, it still lags behind compared to other tourism products that the country has to offer. Therefore, the purpose of this study is to identify the capabilities that homestays should possess in order to improve their performance and bring them on par with the other tourism products that Malaysia has to offer. Based on the Resource Based View (RBV) theory, this study aims to investigate how homestay capabilities can improve the performance of homestays. To achieve the objective, a self-administered questionnaire was distributed to 120 homestay operators across Sabah, registered with Malaysian Homestay Program, which is under the Ministry of Tourism, Arts and Culture Malaysia (MOTAC). 100 questionnaires were returned, of which 94 were analyzed using Smart PLS 3.0 software. All three variables (dynamic capability, innovation capability, and social media marketing capability) tested in this research on the performance of homestays in Sabah were found to be significant. Overall, dynamic capability was found to be the most significant factor in determining homestay performance. The findings suggest that homestays need to emphasize on all these capabilities to be able to improve their performance, and be competitive in the tourism industry. It is also suggested that operators should focus on developing their innovation capabilities as this is important but has a relatively low performance.